2020
DOI: 10.1089/gtmb.2020.0079
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of Circular RNAs Expression in Bladder Carcinoma: A Meta-Analysis

Abstract: Background: Circular RNAs (circRNAs), a type of noncoding RNA, are associated with the occurrence and development of cancers. In recent years, their potential as biomarkers for bladder cancer (BC) has attracted increased attention. Aims: To reveal the value of circRNAs in the prognosis of BC. Methods: Relevant studies were collected to extract the clinicopathological data and overall survival (OS) of patients with BC. We then evaluated their tumor-related clinicopathological indicators using pooled odds ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Moreover, most patients are diagnosed too late and thus have a poor prognosis. Even where surgical resection is possible, the prognosis of GBC is still unsatisfactory ( Dwivedi et al, 2015 ; Wang S. et al, 2020 ). Hence, it is urgent to discover effective early biomarkers and therapeutic targets.…”
Section: Circmto1 In Various Human Cancersmentioning
confidence: 99%
“…Moreover, most patients are diagnosed too late and thus have a poor prognosis. Even where surgical resection is possible, the prognosis of GBC is still unsatisfactory ( Dwivedi et al, 2015 ; Wang S. et al, 2020 ). Hence, it is urgent to discover effective early biomarkers and therapeutic targets.…”
Section: Circmto1 In Various Human Cancersmentioning
confidence: 99%
“…As shown by Li et al, abnormally expressed circRNAs have demonstrated promising potential as diagnostic biomarkers in colorectal cancer and prognostic factors to determine the overall survival in these populations 27 . Furthermore, Wang et al proposed that certain circRNAs are associated with the prognosis and clinicopathological features of bladder cancer patients 28 . As discussed in this study, circMYLK regulates pivotal signaling pathways and cancer‐related cellular processes, including cell proliferation, invasion, and apoptosis through miRNA modulation.…”
Section: Discussionmentioning
confidence: 56%
“… 27 Furthermore, Wang et al proposed that certain circRNAs are associated with the prognosis and clinicopathological features of bladder cancer patients. 28 As discussed in this study, circMYLK regulates pivotal signaling pathways and cancer‐related cellular processes, including cell proliferation, invasion, and apoptosis through miRNA modulation. Moreover, circMYLK can be a valuable prognostic factor in various cancers, including HCC, renal cancer, bladder cancer, NSCLC, ovarian cancer, and colorectal cancer.…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, circ-ITCH can be used as a molecular therapeutic target and prognostic marker for human cancer. Siyuan Wang and Shengqiang Fu also confirmed that circ-ITCH is associated with better clinicopathological indicators, and circ-ITCH has potential as a biomarker ( 83 ).…”
Section: Discussionmentioning
confidence: 82%